2007
DOI: 10.1007/s10577-006-1101-2
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype diversity and the origin of grapefruit

Abstract: Grapefruit is a group of citrus of recent origin, probably resulting from a cross between pummelo and sweet-orange. Aiming to investigate this putative origin and the genetic variability among grapefruit cultivars, the karyotype of six grapefruits, two pummelos, and one tangelo cultivar (grapefruit x tangerine) were analyzed using sequential CMA/DAPI double staining and FISH with rDNA probes. The karyotypes of grapefruit 'Duncan' and 'Foster' differ from those of 'Flame', 'Henderson', 'Marsh' and 'Rio Red'. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 21 publications
7
78
0
1
Order By: Relevance
“…5), some centromeric regions of 'Nanpu' tangor showed small green signals by C. schweinfurthii genomic probe. Matsuyama et al (1996Matsuyama et al ( , 1999 and Moraes et al (2007) reported rDNA sites and a large number of simple sequence repeats in the telomeric and centromeric regions of Citrus. Moraes et al (2007) also revealed that type A chromosomes of some grapefruits (C. paradise Macfad.)…”
Section: Resultsmentioning
confidence: 99%
“…5), some centromeric regions of 'Nanpu' tangor showed small green signals by C. schweinfurthii genomic probe. Matsuyama et al (1996Matsuyama et al ( , 1999 and Moraes et al (2007) reported rDNA sites and a large number of simple sequence repeats in the telomeric and centromeric regions of Citrus. Moraes et al (2007) also revealed that type A chromosomes of some grapefruits (C. paradise Macfad.)…”
Section: Resultsmentioning
confidence: 99%
“…A complementary approach that can be used for karyotype characterization is double fluorescent banding with DAPI and CMA fluorochromes, which discriminates between ATand GC-rich DNA regions. FISH experiments combined with CMA/DAPI staining facilitated effective identification of homologous chromosomes in uniform karyotypes of Citrus paradisi [11], Lilium [12] and Pinus [13]. rDNA sequences are widely used as chromosomal landmarks in cytogenetic studies.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of ribosomal RNA gene (rDNA) sites using FISH offers essential information on phylogenic relationships and on the evolution of given species (Fukui et al, 1994). In citrus, the number and location of rDNA sites in various accessions have been detected (Brasileiro-Vidal et al, 2007;Carvalho et al, 2005;Matsuyama et al, 1996;Miranda et al, 1997a;Morares et al, 2007aMorares et al, , 2007bOllitrault et al, 2000;Pedrosa et al, 2000;Roose et al, 1998). However, these results were limited to the genus Citrus to Poncirus and Fortunella, two very closely related genera.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the relationship between chromosomal regions containing rDNA sites and heterochromatic regions stained by CMA (Brasileiro-Vidal et al, 2007;Carvalho et al, 2005;Matsuyama et al, 1996;Miranda et al, 1997a;Morares et al, 2007aMorares et al, , 2007bPedrosa et al, 2000). These combined analyses have been more informative than any single analysis of just rDNA sites or CMA staining alone.…”
Section: Introductionmentioning
confidence: 99%